Haemangiopericytoma of the mandible - Thiele, Oliver C.; Freier, Kolja; Flechtenmacher, Christa; Rohde, Stefan; Hofele, Christof; Mühling, Joachim; Seeberger, Robin (Journal of cranio-maxillofacial surgery, 2010)
Haemangiopericytomas (HPCs) found in bony structures are rare sarcomas of vascular origin. Here, we report the case of a 41-year-old female with a HPC originating in the right ramus of the mandible. After tumour staging and biopsy for histological reference the tumour was surgically removed. The surgical technique is described and therapy options of these rare cases are discussed and compared with these cases already documented. To the best of our knowledge, this is the 6th case of mandibular HPC reported in the literature.